A vertically and temporally diverse bacterial community in a shallow lake-water sediment site of a eutrophic lake. Issue 2 (3rd April 2021) - Moschos, Stefanos; Piperagkas, Odysseas; Karayanni, Hera
ABSTRACT: Aquatic sediment accumulates organic matter and provides microenvironments for the growth of a diverse microbial community with key roles in the biogeochemical nutrient cycling of the lacustrine ecosystem. We investigated vertical and temporal variations of the sedimentary bacterial community composition in a shallow coastal site of eutrophic Lake Pamvotis (northwestern Greece) across 3 horizons between the surface and 5 cm below lake floor (cmblf) during transition to the cold period of the year (Oct–Dec). For this analysis we used Illumina sequencing of the V3–V4 hypervariable regions of the 16S rRNA gene. Bacterial community composition was dominated by Proteobacteria, Bacteroidetes, and Chloroflexi . Rare operational taxonomic units (OTUs) represented 96.09% (standard deviation 0.61%) of richness per sample, contributing significantly to diversity, and only a few became abundant during the study. Abundant OTUs represented <0.005% of richness but accounted for 20–33% of reads in different samples, mainly associated with anaerobic/microaerobic taxa common in polluted aquatic systems, sludge digesters, or wastewater (e.g., Thiolamprovum pedioforme, Candidatus Competibacter, Petrimonas ). About 50% of OTUs found at the surface persisted with depth while shared OTUs between any 2 months were always >70% of richness. Overall, sediment bacterial community composition was diverse but remained largely homogeneous in the sediment of this human-impacted ecosystem at the temporal and vertical scale studied here. The study revealed the potential of specific bacterial taxa (e.g., Anaerolineae, Bellilinea ) to serve as monitors of specific pollutants (e.g., polycyclic aromatic hydrocarbons) as well as the need to investigate the role of the rare biosphere in ecosystem functioning.